GE_GERICHTE P/896/2018 vom 3. März 2020 - GE Cour de justice (2020)
LÉSION CORPORELLE SIMPLE;IN DUBIO PRO REO;FIXATION DE LA PEINE;INDEMNITÉ(EN GÉNÉRAL) | CP.123.al1; CP.123.al2.ch1; CP.15; CP.16; CP.47; CP.52; CP.433